Penggunaan teknologi dalam pengukuran kekuatan otot pasien kritis: A scoping review - Suhartini Ismail; Septiani Pramanasari; Rifky Ismail (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Patients treated in the intensive care unit often experience decreased muscle strength. Continuous muscle weakness will affect muscle condition and have a bad impact and can cause disability. Health workers can use technology to measure muscle strength. Purpose: To examine in depth the technology for measuring muscle strength in critical patients. Method: Scoping review research was conducted in March 2023 using PubMed, ScienceDirect, Scopus, and ProQuest databases published in 2018-2023. Identified and selected through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines. The inclusion criteria used include muscle strength measurement technology and research participants in critical patients, articles published between 2018-2023, articles that are open access, in English, and relevant. Screening and selection of articles was carried out on the title and abstract, eliminating duplicate articles, articles with full text, according to the research field, type of method, randomized controlled trials and systematic reviews. Results: Identified 663 articles and obtained 10 relevant articles for analysis summarizing the development of technology for measuring muscle strength in critical patients, the nursing implications of technology in assessing muscle strength, and the ease and use of technology in measuring muscle strength. Conclusion: Technological developments have a positive impact on patient treatment, especially for patients with critical conditions who require fast and appropriate treatment so that their quality of life can improve. Utilizing technological developments in accurately measuring muscle strength in critical patients can have a positive impact in selecting the appropriate patient treatment and rehabilitation process as well as preventing complications or muscle contractures. Suggestion: Further research regarding technological innovations in muscle strength in critical patients’ needs to be carried out in more depth because it is useful in helping nurses and health service providers in measuring muscle strength in critical patients, so that it is beneficial for critical patients and provides accurate and valid muscle strength measurement results. Keywords: Critical Patients; Measurement; Muscle Strength; Technology. Pendahuluan: Pasien yang dirawat di ICU sering mengalami penurunan kekuatan otot. Kelemahan otot yang terus menerus akan mempengaruhi kondisi otot dan berdampak buruk serta dapat menyebabkan kecacatan. Penggunaan teknologi dapat dimanfaatkan oleh tenaga kesehatan dalam pengukuran kekuatan otot. Tujuan: Untuk mengkaji secara mendalam teknologi dalam pengukuran kekuatan otot pada pasien kritis. Metode: Penelitian scoping review dilakukan pada bulan Maret 2023 melalui database PubMed, ScienceDirect, Scopus, dan ProQuest terbitan tahun 2018-2023. Diidentifikasi dan diseleksi melalui Preferred Reporting Items for Systematic Review and Meta-Analysis for Scoping Review guideline (PRISMA-ScR). Kriteria inklusi yang digunakan adalah memuat teknologi pengukuran kekuatan otot dan partisipan penelitian pada pasien kritis, artikel diterbitkan antara tahun 2018-2023, artikel bersifat open acces, berbahasa Inggris, dan relevan. Penyaringan dan pemilihan artikel dilakukan pada judul dan abstrak, menghapus artikel duplikat, artikel dengan teks lengkap, sesuai dengan bidang penelitian, jenis metode randomized controlled trial dan systematic review. Hasil: Mengidentifikasi 663 artikel dan mendapatkan 10 artikel relevan untuk dianalisis merangkum tentang perkembangan teknologi pengukuran kekuatan otot pada pasien kritis, implikasi keperawatan terhadap teknologi dalam penilaian kekuatan otot, dan kemudahan serta penggunaan teknologi dalam pengukuran kekuatan otot. Simpulan: Perkembangan teknologi memberikan dampak positif terhadap pengobatan pasien, terutama pada pasien dengan kondisi kritis yang memerlukan pengobatan cepat dan tepat agar kualitas hidupnya dapat ditingkatkan. Penggunaan perkembangan teknologi dalam pengukuran kekuatan otot secara akurat pada pasien kritis dapat berdampak positif pada pemilihan proses pengobatan, rehabilitasi yang tepat bagi pasien dan mencegah terjadinya komplikasi maupun kontraktur otot. Saran: Penelitian lebih lanjut mengenai inovasi teknologi kekuatan otot pada pasien kritis perlu dilakukan lebih mendalam karena bermanfaat dalam membantu perawat dan penyedia layanan kesehatan dalam mengukur kekuatan otot pada pasien kritis, sehingga akan bermanfaat bagi pasien kritis dan memberikan hasil pengukuran kekuatan otot yang tepat dan valid. Kata Kunci: Kekuatan Otot; Pasien Kritis; Pengukuran; Teknologi.